Regarding the Issue on Multidisciplinary Forensic Examinations to Establish the Fact of Contact Interaction - K. P. Sylenok; O. Y. Hrosheva (Bulletin of Kharkiv National University of Internal Affairs)
The authors of the article analyze theoretical developments on the status of multidisciplinary forensic examinations. Attention is paid to the analysis of the state of legal and methodological support in the appointment and conduct of multidisciplinary forensic examinations. On the example of multidisciplinary forensic examination on the establishment of the fact and circumstances of objects contact interaction, the authors have demonstrated the insufficiency of methodological support in this area and have substantiated the need to develop common and individual methods.